Pengaruh Pemberdayaan SDM dan Lingkungan Kerja terhadap Kepuasan Kerja Serta Dampaknya pada Kinerja Aparatur Sipil Negara Kecamatan Paal Merah Kota Jambi - Tri Fitri Yanti; Saiyid Syeikh; Ali Akbar (Universitas Batanghari, 2023)
The purpose of this study is to describe HR empowerment, work environment, job satisfaction and employee performance in Paal Merah District, Jambi City and to analyze the effect of HR empowerment and work environment partially and simultaneously directly and indirectly on job satisfaction and employee performance, as well as to analyze job satisfaction. on employee performance. To answer the research objectives, this research is supported by theoretical studies related to research variables, namely human resource empowerment, work environment, job satisfaction, and performance. In addition, the author also seeks relevant previous research in the form of previous articles/journals and theses to support this research. The population in this study are employees of the Paal Merah District, Jambi City, totaling 80 employees with conditions in 2022. Data analysis techniques used in this study namely through path analysis followed by hypothesis testing through the F test (Simultaneous) and t test (Partial). From the path analysis tests carried out, it was found that HR empowerment and the work environment have an influence on job satisfaction and employee performance, both directly and indirect. This explains that if the organization has good empowerment and a better work environment then this will further increase employee job satisfaction with the organization and provide maximum work results. This study concludes HR Empowerment, Work Environment, Job Satisfaction and employee performance in conditions that Good. In addition, empowerment of human resources and work environment partially and simultaneously has a positive and significant impact on job satisfaction and employee performance in Paal Merah District, Jambi city. Likewise, job satisfaction has a positive and significant influence on employee performance.